Industrial production: Pursuing scale expansion or pollution reduction? Judgment based on the Copeland-Toylor model. (10th April 2019) - Yang, Guanglei; Zhang, Wei; Zha, Donglan
Abstract: Based on the Copeland-Toylor model, this paper constructs a mathematical model to analyze the impact of industrial production scale expansion on the discharge of industrial pollutants. The analysis shows that expanding the industrial production scale can increase industrial pollution emissions. Due to the uneven distribution of the industrial production scale and emissions of industrial waste in the spatial pattern, the effect of the industrial production scale on industrial waste emissions differs among regions. This model is then applied to the panel data of 30 provinces in China from 2000 to 2015. The results show that the industrial production scale can aggravate the discharge of industrial pollutants, and the effect on industrial waste water is considerably stronger than that of both industrial waste gas and industrial waste. Moreover, the impact on micro pollutant emissions shows apparent regional differences. Based on the theory of externality, governmental action should balance the social gains of industrial production with the social costs of pollution.